Are Audience Preferences for Electronic Cinema Affected by Preferences in Indonesian Movie Choices? - Hidayat, Endik; Susilo, Daniel; Mujiono, Mujiono (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2023)
Electronic cinema has transformed the worldwide movie industry by providing spectators with various movie content on digital platform. Filmmakers, distributors, and content creators must understand consumer preferences as electronic cinema develops popularity. This study examines whether Indonesian movie tastes affect electronic cinema preferences. Indonesia, with its rich cultural legacy and growing film industry, is an excellent case study for studying movie preferences and electronic cinema adoption. This article examines how Indonesian moviegoers’ digital movie choices affect their overall movie tastes. This paper examined a comprehensive investigation of audience viewing trends on electronic cinema platforms, polls, and interviews with Indonesian moviegoers reveal their cinematic preferences. Demographics, socio-cultural issues, and technology advances also influence audience preferences, which the study seeks to understand. This research goes beyond audience behaviour. Utilising survey within 148 respondents among Greater Jakarta Metropolitan area and analysing using SMART PLS Software. The findings may help filmmakers and content creators appeal to Indonesian viewers. Distributors and digital platforms can also tailor their offers to Indonesian tastes to boost electronic cinema growth. This study illuminates Indonesian movie tastes and electronic cinema choices, contributing to film studies and audience behaviour research. It bridges conventional movie-watching habits with the digital age, providing significant information into Indonesia’s and other countries’ film consumption.Keywords: Audience preferences, electronic cinema, movie choices ABSTRAKSinema elektronik telah mengubah industri film di seluruh dunia dengan menyediakan berbagai film kepada penonton konten di platform digital. Pembuat film, distributor, dan pembuat konten harus memahami preferensi konsumen seiring berkembangnya popularitas sinema elektronik. Penelitian ini menguji apakah selera film Indonesia memengaruhi preferensi bioskop elektronik. Indonesia, dengan warisan budaya yang kaya dan industri film yang berkembang, merupakan studi kasus yang bagus untuk mempelajari preferensi film dan adopsi sinema elektronik. Artikel ini mengkaji bagaimana penonton bioskop Indonesia pilihan film digital memengaruhi selera film mereka secara keseluruhan. Makalah ini mengkaji penyelidikan komprehensif terhadap tren tontonan penonton di platform sinema elektronik, polling, dan wawancara dengan penonton bioskop Indonesia mengungkapkan preferensi sinematik mereka. Demografi, permasalahan sosial budaya, dan kemajuan teknologi juga turut memengaruhi preferensi audiens, yang ingin dipahami studi ini. Penelitian ini melampaui perilaku penonton. Memanfaatkan survei terhadap 148 responden di wilayah Metropolitan Jabodetabek dan menganalisis menggunakan SMART Perangkat Lunak PLS. Temuan ini dapat membantu pembuat film dan pembuat konten untuk menarik perhatian pemirsa di Indonesia. Distributor dan platform digital dapat menyesuaikan penawaran mereka dengan selera orang Indonesia untuk meningkatkan pertumbuhan sinema elektronik. Studi ini menerangi selera film Indonesia dan pilihan sinema elektronik, berkontribusi pada studi dan penelitian perilaku penonton film. Ini menjembatani kebiasaan menonton film konvensional dengan era digital, memberikan dampak signifikan informasi mengenai konsumsi film di Indonesia dan negara lain.Kata Kunci: Preferensi audiens, sinema elektronik, selera penonton